The application of multi-criteria decision analysis in evaluating the value of drug-oriented intervention: a literature review - Su, Pengli; Zhi, Kai; Xu, Huanhuan; Xiao, Jing; Liu, Jun; Wang, Zhong; Liu, Qiong; Yu, Yanan; Dang, Haixia (Frontiers in Pharmacology, 2024)
MCDA has gained increasing attention in supporting drug risk-benefit assessment, pricing and reimbursement, as well as optimization of clinical interventions. The objective of this study was to systematically collect and categorize evaluation criteria and techniques of weighting and scoring of MCDA for drug value assessment. A systematic review of the literature was conducted across seven databases to identify articles utilizing MCDA frameworks for the evaluation of drug value. Evaluation criteria mentioned in the included studies were extracted and assigned to 5 dimensions including clinical, economic, innovative, societal and humanistic value. A descriptive statistical analysis was performed on the identified drug value evaluation criteria, as well as the weighting and scoring techniques employed. The more a criterion or technique were mentioned in articles, the more important we consider it. Out of 82 articles included,111 unique criteria were identified. Among 56 unique criteria (448 times) used to measure clinical value, the most frequently mentioned were “comparative safety/tolerability” (58 times), “comparative effectiveness/efficacy” (56 times), “comparative patient-perceived health/patient reported outcomes” (37 times), “disease severity” (34 times), and “unmet needs” (25 times). Regarding economic value measurement, out of 20 unique criteria (124 times), the most frequently utilized criteria were “cost of intervention” (17 times), “comparative other medical costs” (16 times), and “comparative non-medical costs” (18 times). Out of 10 criteria (18 times) for assessing innovative value,“a novel pharmacological mechanism” was the most frequently mentioned criterion (5 times). Among 22 criteria (73 times) used to measure societal value,“system capacity and appropriate use of intervention” was the most frequently cited criterion (14 times). Out of 3 criteria (15 times) utilized to measure humanistic value,“political/historical/cultural context” was the most frequently mentioned criterion (9 times). Furthermore,11 scoring and 11 weighting techniques were found from various MCDA frameworks. “Swing weighting” and “a direct rating scale” were the most frequently used techniques in included articles. This study comprehensively presented the current evaluation dimensions, criteria, and techniques for scoring and weighting. By highlighting the frequently cited evaluation criteria and techniques for scoring and weighting, this analysis will provide a foundation to reasonably select appropriate evaluation criteria and technique in constructing MCDA framework.